Análisis de valoración del uso de las NTIC1 en la gestión escolar - Bermúdez De Armas, Jhonis Enrique
In the following article you will find the results of the research carried out in the city of Bogotá D. C., after applying the measurement instrument “Matrix of assessment of new technologies of information and communication (NTICs) in school management”. The research focuses on the applicability of NTICs in the administrative and academic management of educational institutions in Bogotá, Colombia.The research article is addressed as follows:Chapter 1. Introduction, research perspective in school management.Chapter 2. Methodology, addresses the subject researched from the theoretical support.Chapter 3. Results obtained at the end of the research about the applicability of assessment of the use of NTICs in school management.Chapter 4. Conclusions, the researcher’s view of the results obtained in the research.Chapter 5. Bibliography, theoretical support of research.The aspects analyzed are academic management, administrative-financial management, community management and direction management. The research seeks to evidence factors that must be strengthened to correctly apply NTICs in the educational institutions analyzed, located in the city of Bogotá, Colombia.